Drug-coated balloon in the treatment of coronary left main true bifurcation lesion: A patient-level propensity-matched analysis - Pan, Liang; Lu, Wenjie; Han, Zhanying; Pan, Sancong; Wang, Xi; Shan, Yingguang; Peng, Meng; Qin, Xiaofei; Sun, Guoju; Zhang, Peisheng; Dong, Jianzeng; Qiu, Chunguang (Frontiers in Cardiovascular Medicine, 2022)
Aims An increasing body of evidence suggests that drug-coated balloon (DCB) angioplasty represents a valuable option for revascularization in selected patients with coronary bifurcation disease. However, there remains a paucity of real-world observational evidence on the efficacy of DCB in left main (LM) true bifurcation lesion. We compared clinical and angiographic outcomes of hybrid [DCB + drug-eluting stent (DES)] versus DES-only strategy (provisional stenting or two-stent strategies) in de novo LM true bifurcated lesions. Methods The primary endpoint was the 2-year composite rate of target lesion failure (TLF): cardiac death, target vessel myocardial infarction (TVMI), or clinically driven target lesion revascularization (CD-TLR). A routine 1-year angiographic follow-up was scheduled. Propensity-score matching was utilized to assemble a cohort of patients with similar baseline characteristics. Results Among 1077 eligible patients, 199 who received DCB treatment and 398 who were assigned to DES therapy had similar propensity scores and were included in the analysis. TLF within 2 years occurred in 13 patients (7.56%) assigned to DCB group, and 52 patients (14.36%) assigned to DES group (odds ratio: 0.487; 95% confidence interval: 0.258–0.922; P = 0.025; Log-rank P = 0.024). Compared with the DES group, the DCB group resulted in a lower rate of CD-TLR (2.91% vs. 9.42%; P = 0.007). Cardiac death, TVMI, all-cause mortality, and stent thrombosis were comparable between both groups. Patients treated with DES-only were associated with a higher late lumen loss (0.42 ± 0.62 mm vs. 0.13 ± 0.42 mm, P < 0.001) compared with the DCB group at 1 year. In sensitivity analysis, the DCB group also presented a lower incidence of TLF, CD-TLR and stent thrombosis both compared to the two-stent strategy and compared to provisional stenting (Ps < 0.05). Conclusion The 2-year results of PCI utilizing DCB for LM true bifurcation lesions are superior to employing DES alone in terms of safety and effectiveness.